Blocking probability of the reverse link cellular CDMA system - Kumpairee, C.; Kimpan, C.; Pin-Ngern, O.; Hemmakorn, N.; Noppanakeepong, S. (My University, 2002)
The blocking probability of the reverse link cellular CDMA system is presented. Gaussian and lognormal approximation are the methods for determination of blocking probability. In the analysis in this paper, the parameter for the number of resolvable paths over a Rayleigh multipath fading channel is presented. In addition, we also show the effect of power control errors.
Keywords: Bandwidth; Base stations; Error correction; Fading; Frequency; Multiaccess communication; Multiple access interference; Power control; Power system modeling; Rayleigh channels